2017
DOI: 10.1002/aqc.2797
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of recreational spearfishers and its impacts on corals

Abstract: 1. Recreational diving is a concern regarding its effects on benthic assemblages, especially on heavily dived coral reefs. However, spearfisher behaviour and the scale of damage they cause to corals remains unknown.2. The behaviour of recreational spearfishers was observed to determine their rate of physical contacts with corals. The experience level and fishes captured by spearfishers were assessed to establish their relationship with the number of contacts with corals.3. All spearfishers made contact with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These findings are not surprising, as a similar study of recreational fishers in the United Kingdom found that they had positive perceptions of the artificial reef effects of wind farms and 73% of anglers surveyed said they would be willing to fish around the perimeter or within a wind farm (Hooper et al, 2017). Although increased abundance of fish can aid fisheries and tourism sectors (Bergström et al, 2014), the increased activity could negatively affect resources and lead to overfishing (Giglio et al, 2018). For instance, Coleman et al (2004) found that recreational fisheries landings comprised 23% of the total landings in the United States in 2002, and for some valued overfished species, recreational landings were greater than commercial landings.…”
Section: Discussionmentioning
confidence: 95%
“…These findings are not surprising, as a similar study of recreational fishers in the United Kingdom found that they had positive perceptions of the artificial reef effects of wind farms and 73% of anglers surveyed said they would be willing to fish around the perimeter or within a wind farm (Hooper et al, 2017). Although increased abundance of fish can aid fisheries and tourism sectors (Bergström et al, 2014), the increased activity could negatively affect resources and lead to overfishing (Giglio et al, 2018). For instance, Coleman et al (2004) found that recreational fisheries landings comprised 23% of the total landings in the United States in 2002, and for some valued overfished species, recreational landings were greater than commercial landings.…”
Section: Discussionmentioning
confidence: 95%
“…One study identified additional effects of recreational spearfishing on marine ecosystems related to inadvertently damaging important habitats such as corals in areas that experience high levels of fishing effort (Giglio et al 2018). However, it is possible that such damage is less than that associated with other fishing methods, because there may be fewer anchor deployments per trip compared to angling (Frisch et al 2008).…”
Section: Discussion Of Ecological Aspectsmentioning
confidence: 99%
“…For example, in the Mediterranean Sea, recreational and commercial fisheries are comparable in terms of catches and economic importance (Lloret et al, 2008; Giovos et al, 2018; Keramidas et al, 2018; Michailidis, Katsanevakis & Chartosia, 2020). Moreover, recreational spearfishing frequently targets larger top‐predators, possibly causing significant trophic cascades on marine ecosystems (Lewin, Arlinghaus & Mehner, 2006; McClenachan, 2009), in addition to reducing the abundance of target species (Frisch et al, 2012; Young, Foale & Bellwood, 2015) and even damaging corals (Giglio et al, 2018). Still, recreational fishing is hardly incorporated in management due to the lack of data, hampering our ability to assess and reduce its impacts on fish populations and marine ecosystems.…”
Section: Introductionmentioning
confidence: 99%